PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIKA SISWA KELAS IV SD NEGERI 5 LANGSA - Afra Safrida, Nur; Ramadhani , Dini; Febri Rafli , Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The background of this study is the low ability to understand Mathematics. This study aims to determine the effect of the problem based learning (PBL) model on the ability to understand Mathematics of fourth grade students of SD Negeri 5 Langsa. Based on the Mann-Whitney U test for non-normally distributed data with a significance level of 0.05, the calculation results show that the Mann-Whitney U value is 157,500 with a Z value of -2.032 and a significance of 0.042. Because the significance value is smaller than <0.05, H0 is rejected and Ha is accepted. It can be concluded that there is an influence on students' ability to understand Mathematics between the experimental class and the control class after using the problem based learning (PBL) model.